(untitled) (Fiep Bulletin - online, 2014)
The child micturitional dysfunction (CMD) is defined as na abnormal micturitional pattern for the age of a child, not being recognized before the acquisition of the daily urinary control. The urinary escapes are socially badly tolerated and understood by child and family members. Thus the individualization and application of a specific treatment is important. The objectives were verifying the effect of a physical therapeutic intervention protocol in CMD; analyzing the evolution of CMD and the changes in the level of satisfaction through the Analogical Visual Scale (AVS); comparing the score of the questionnaire of evaluation of hyperactive bladder and Escore de Farhat before and after the treatment. Clinical study of a case of CMD of a girl, 10 years old, who presented symptoms of CMD. The protocol was composed of 20 sessions, with frequency of 2 days weekly, and consisted of orientations for behavioral reeducation and physical therapeutic intervention with stretching and exercises for the muscular groups involved. The participant answered the evaluation sheet, the questionnaire for evaluation of hyperactive bladder and the Escore de Farhat, and indicated the level of satisfaction in the AVS. The physical therapeutic intervention protocol in CMD used presented benefic effect, shown by the absence of CMD in the end of the same. There was an improvement in the questionnaire of hyperactive bladder, which meant decrease of the hyperactivity. The score of the Escore de Farhat decreased gradually as the episodes of urinary losses did too. There was a change in the level of satisfaction counting that she presented dissatisfied in the presence of CMD, and satisfied when in the absence of the same. The questionnaire of hyperactive bladder, the Escore de Farhat and the level of satisfaction evoluted gradually in proportion that the case of CMD decreased, showing na important relation between the improvement of CMD and the improvement in the case of hyperactive bladder, of the Escore de Farhat and the AVS.